Date: Mar 19, 2012 4:51 AM
Author: Ashraf Samhouri
Subject: Tautology Proof Question
Hello guys,

While studying, I've passed through this proof (in the class notes):

Example:

Proof that:

( (p v q) ^ (p -> r) ^ (q -> r) ) -> r

is a tautology?

The solution is:

( (p v q) ^ (¬p v r) ^ (¬q v r) ) -> r

( (p ^ ¬p) v (r ^ q) ^ (¬q v r) ) -> r

(F v (q ^ ¬q) v r) -> r

r -> r

¬r v r

.: T

Actually I can't understand the steps, am not sure if the notes are

well-written here, but I'll appreciate any help in explaining the

proof.

Regards,

ASH